Word Formation of English Slang in Rich Brian's Album 1999 - Adhani Aditya; Fitrawati Fitrawati (English Language and Literature, 2023)
This research aimed to find the form of slang words and the type of word formation process found in Rich Brian's Album 1999. This type of research was descriptive research. The data of this research was words and phrases of song lyrics in album 1999. For the data collection, the researcher found all the lyrics form the largest collection of song lyrics and music on https://www.genius.com. There were three instruments for this research: the researcher itself, laptop, and table indicators. There were five steps for the data analysis: categorizing the form of slang and type of word formation process, analysed the slang word use the theory, tabulated the data on the table, calculated the percentage, and concluding the research finding. The theory used in this research was the theory of Coleman (2012) and Yule (2010). The result showed from 9 forms of slang words, the researcher found 3 forms of slang words. The 3 types of form of slang words are change in meaning (21,05%), change in function (26,31%), and abbreviation (52,64%). The result showed about the type of word formation process, the researcher found 5 types of word formation process, namely blending (14,03%), clipping (70,18%), derivation (5,27%), and acronym (3,50%). The most dominant form of slang words is abbreviation and the most dominant type of word formation process is clipping. Based on the findings, the relationship between slang and song lyrics is to make the song lyrics more interesting and easier to express ideas.Key words: Morphology, Word formation process, Slang word, Form of slang, Rich Brian’s Song